The ties that bind: Bi-national trade implications of the US and Canada using bi-national freight movement network via border crossings. (September 2015) - Hwang, Ha; Park, JiYoung; Kwon, Changhyun; Friedman, Kathryn; Attard, Nathan; Chang, Shen Hao; Wells, Samuel
Abstract: This study combines US-Canada bi-national highway network data with a freight flow dataset using ports of entry (POE) via highway border crossings. Through several sub-procedures, the US and Canada highway systems are integrated into a single network dataset. In addition, border wait time dataset was monitored and analyzed to set the border delay baseline. This dataset enables us to explore the freight traffic pattern between the US and Canada. Weighted Eigenvector Score is computed using a Social Network Analysis tool. The results demonstrate that major regional bodies are the primary users of major POE between the US and Canada. This study not only offers an improved understanding of the economic implications of US–Canada border crossings, but also contributes to developing a simulation tool, a bi-national Transportation-combined National Interstate Economic Model. Such a tool is expected to extend and apply to other contexts, such as transportation and national and bi-national security, among other applications. Additionally, this study suggests several important considerations for US and Canadian officials charged with devising policy to protect against security threats while facilitating legitimate flows of goods, services and people across the border. Highlights: We developed a bi-national freight network model connecting freight flows of trucks between the US and Canada. We analyzed border wait times that are essential for the bi-national TransNIEMO to operate. Weighted Eigenvector Scores reveal Detroit, Buffalo, Port Huron, Blaine-Pacific Highway, and Champlain as the most important ports of entry. While freight flows are dispersed to many US states, Canadian freight flows tend to stay within the province of their ports of entry.